2021
DOI: 10.3389/fpsyt.2021.780276
|View full text |Cite
|
Sign up to set email alerts
|

Supported Decision-Making in Persons With Dementia: Development of an Enhanced Consent Procedure for Lumbar Puncture

Abstract: The right to make autonomous decisions is enshrined in law. However, the question how persons with cognitive deficits can be enabled to make autonomous decisions has not been satisfactorily addressed. In particular, the concept of supported decision-making and its implementation into practice has been poorly explored for persons with dementia (PwD).This article describes the empirical development and implementation of support tools to enhance informed consent processes (so called enhanced consent procedures/EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…Die empirische Evidenz für die Effektivität von Maßnahmen der Entscheidungsassistenz bei psychischen Erkrankungen ist zwar noch begrenzt [ 18 ], aber in diesem Kontext kann z. B. an verbesserte Einwilligungsverfahren und die Einbeziehung von Genesungsbegleitern oder anderen Assistenzpersonen gedacht werden [ 19 ].…”
Section: Das Kombinierte Modell Der Entscheidungsassistenzunclassified
“…Die empirische Evidenz für die Effektivität von Maßnahmen der Entscheidungsassistenz bei psychischen Erkrankungen ist zwar noch begrenzt [ 18 ], aber in diesem Kontext kann z. B. an verbesserte Einwilligungsverfahren und die Einbeziehung von Genesungsbegleitern oder anderen Assistenzpersonen gedacht werden [ 19 ].…”
Section: Das Kombinierte Modell Der Entscheidungsassistenzunclassified
“…It was previously shown that, for example, uncertainties about lumbar punctures could be reduced by means of standardized video education (Babapour Mofrad et al, 2021). Proposals for supported decision-making with persons with dementia were also published recently (Wied et al, 2021) and could serve as a helpful tool for obtaining informed consent even in cases of already established cognitive impairment, thereby enabling autonomy. However, the concerns about lumbar punctures highlight the importance of replacing this examination with serum parameters in the future (Nabers et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As in our previous studies, the presentation of information will be standardised for both the intervention and the control settings in order to ensure as much consistency as possible in everything apart from the ‘place’. Consequently, all support strategies that have proven to be effective in our own and international studies (e.g., elaborated plain language, key word list, time of day: 8–15 o’clock, person-centred attitude), will be used in both places (as recommended in the current AWMF-S2k-guideline “Einwilligung von Menschen mit Demenz in medizinische Maßnahmen”; for a summary of available evidence on SDM for PwAD, see [ 7 , 19 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research into supported decision-making (SDM) in PwAD has focused on the use of SDM strategies like keyword lists, elaborated plain language, and visualisation to compensate for deficits in verbal retrieval and improve a person’s understanding of information [ 7 ]. We consider SDM to be a communicative process and base our understanding of it on the combined communication model of Haberstroh et al [ 8 ], in which the mentioned strategies support both verbal and non-verbal content aspects of communication.…”
Section: Introductionmentioning
confidence: 99%